Evaluation of Cystic Echinococcosis Cases in Terms of Sociodemographic, Clinical and Hospitalization Features in Karaman Province, Turkey - Mehmet Fatih AYDIN; Emre ADIGÜZEL (Tehran University of Medical Sciences, 2019)
Background: We aimed to investigate the cystic echinococcosis (CE) epidemiology in Karaman Province from 2010 to 2017 using data from the provincial state hospital. Methods: Overall, 482 cases were determined from Karaman State Hospital, Karaman Province, Turkey from 2010 to 2017. Records were investigated in terms of year, gender, age, cyst location, rural and urban households and duration of hospital stay. Results: The CE incidence was 22.40 per 100 000 people after final diagnosis with focused abdominal ultrasound. Totally, 482 people including 166 (34.4%) male and 316 (65.6%) female were with CE. The mean age of patients was 50.3±17.48 yr. More CE cases were reported in the age group of 51-60 yr than in the other age groups. CE was mostly seen in liver (470, 97.5%). Moreover, 28.4% of patients were resided in rural areas. The observed frequencies of demographic features of female gender, infected liver, residence in provincial centers, referral to general surgery policlinic and no hospitalization were significantly higher than expected frequencies (P<0.05). Sixty (12.4%) patients with CE had been hospitalized. There was a statistically significant positive relationship between age of hospitalized patients and duration of hospitalization (P<0.05). Of the patients 73.2% were admitted to general surgery. Conclusion: CE is of great importance to public health considerations in the Karaman Province and we advocate the implementation of eradication programs to decrease the CE cases number.